A THE INFLUENCE OF ISLAMIC WORK ETHICS AND MEANINGFUL WORK ON EMPLOYEE PRODUCTIVITY IN THE DIGITAL WORK ERA - Kuncorosidi Kuncorosidi (STIESA Press, 2026)
ABSTRACT This study examines the influence of Islamic Work Ethics (IWE) and Meaningful Work (MW) on employee productivity among Generation Z workers in digital-based coffee shop enterprises in West Java Province, Indonesia. Grounded in Human Capital Theory, Self-Determination Theory, and Islamic Work Ethics Theory, this quantitative explanatory research employs multiple linear regression analysis. Using purposive sampling, data were collected from 384 Generation Z employees working at digitally operated coffee shops including Kopi Kenangan, Fore Coffee, Tomoro Coffee, and Janji Jiwa across eleven sub-regions of West Java. Results demonstrate that Islamic Work Ethics has a significant positive influence on employee productivity (? = 0.412, p < 0.001), and Meaningful Work exerts a significant positive influence on employee productivity (? = 0.387, p < 0.001). Simultaneously, both variables explain 61.4% of the variance in employee productivity (R² = 0.614, F = 152.73, p < 0.001). These findings indicate that integrating ethical work orientation grounded in Islamic values with purpose-driven work engagement constitutes a robust framework for enhancing operational productivity in modern digital work environments. The study contributes to the literature by offering empirical evidence on the role of ethical-spiritual work orientation in shaping productivity among a Generation Z workforce navigating digital transformation.